Vitamin D binding protein genetic isoforms, serum vitamin D, and cancer risk in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial. - Stephanie J Weinstein; Dominick Parisi; Alison M Mondul; Tracy M Layne; Jiaqi Huang; Rachael Z Stolzenberg-Solomon; Regina G Ziegler; Mark P Purdue; Wen-Yi Huang; Christian C Abnet; Neal D Freedman; Kai Yu; et al. (PLoS ONE)
Associations between vitamin D biochemical status and cancer may be modified by vitamin D binding protein isoforms which are encoded by GC (group-specific component). We examined interactions between serum 25-hydroxyvitamin D [25(OH)D], the Gc isoforms Gc1-1, Gc1-2, and Gc2-2, and cancer risk within the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial cohort based on 3,795 cases and 3,856 controls. Multivariable-adjusted logistic regression models estimated odds ratios (ORs) and 95% confidence intervals (CIs) of cancer risk according to 25(OH)D quantiles, stratified by Gc isoform. Separately, the GC-cancer risk association was examined using proportional hazards regression among 109,746 individuals with genetic data and 26,713 diagnosed with cancer. Specific vitamin D binding protein isoform subtypes were delineated and analyzed, including Gc1-1 subtypes (Gc1s-Gc1s, Gc1f-Gc1s, and Gc1f-Gc1f) and Gc2 subtypes (Gc1s-Gc2, Gc1f-Gc2, and Gc2-Gc2). For most cancers, the GC genotype did not modify the risk associations for 25(OH)D; e.g., the OR for high vs. low vitamin D quintile was 1.09 (0.89-1.33) for overall cancer risk among individuals with the Gc1-1 isoform and 1.04 (0.83-1.31) among those with either the Gc1-2 or Gc2-2 isoforms. ORs for high compared to low vitamin D tertile for colorectal, lung, breast, and prostate cancer among those with the Gc1-1 vs. any Gc2 isoforms were, respectively, 0.60 vs. 0.73, 1.96 vs. 1.03, 1.30 vs. 1.18, and 1.19 vs. 1.22 (all p-interaction ≥0.36). However, GC qualitatively modified the vitamin D-bladder cancer risk association: OR = 1.70 (95% CI 0.96-2.98) among those with the Gc1-1 isoform and 0.52 (0.28-0.96) among those with any Gc2 isoforms (p-interaction = 0.03). When modeled without regard for 25(OH)D, Gc isoforms were generally not associated with cancer risk, although melanoma risk was significantly lower among individuals with the "f" subtype of the Gc1-1 isoform, specifically HR = 0.83 (95% CI 0.70-0.98) for Gc1f-1s and 0.67 (0.45-1.00) for Gc1f-1f, compared to individuals with the Gc1s-Gc1s isoform. Vitamin D binding protein genetic isoforms may be associated with melanoma risk but do not modify the association between vitamin D status and cancer, with the possible exception of bladder cancer.